Akulturasi budaya dalam tradisi ’manganan’ (sedekah laut) di Pesisir Pantai Palang Tuban - Yaqin, Ahmad Ainul (Maliki Interdisciplinary Journal, 2024)
The tradition of “Manganan’ or sedekah laut is an important part that is continuously carried out by Palang villagers every year. This tradition has a philosophical and historical value as a form of expression of gratitude for the local community for all the abundant gifts of the sea. The tradition of sedekah laut has undergone changes along with the strengthening of the Islam of fishermen and communities around the coast. Many Islamic values influence the almsgiving tradition, so you can find a strong form of acculturation between the original culture, in the form of larung sajen, and a new culture that is in accordance with Islam. This study aims to find out how the form of acculturation of sedekah laut culture exists in the Palang Tuban village community. The method used is to use descriptive qualitative by looking at the entire existing history. The results of the study indicate that there is acculturation of the culture of sedekah laut in the Palang Tuban village community along with the existing Islamic influence and the strengthening of the Islam of fishermen and surrounding coastal communities.